Chemistry structure and properties - Tro, Nivaldo J. (Always learning, 2015)
Bestselling author Nivaldo Tro's premise is that matter is particulate--it is composed of molecules; the structure of those particles determines the properties of matter. This core idea is the inspiration for his seminal text--Chemistry: Structure and Properties. Dr. Tro emphasizes the relationship between structure and properties, establishes a unique approach to teaching chemistry by presenting atomic and bonding theories early in the course, and stresses key concepts and themes in text, images, and interactive media. The book is organized to present chemistry as a logical, cohesive story from the microscopic to the macroscopic, so students can fully grasp the theories and framework behind the chemical facts. Each topic is carefully crafted to convey to students that the relationship between structure and properties is the thread that weaves all of chemistry together.